2006
DOI: 10.1007/s00464-006-9027-5
|View full text |Cite
|
Sign up to set email alerts
|

Impact of previous abdominal surgery on laparoscopic appendectomy for acute appendicitis

Abstract: Previous abdominal surgery, whether upper or lower abdominal, has no significant impact on laparoscopic appendectomy for acute appendicitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
17
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 12 publications
2
17
0
2
Order By: Relevance
“…Dealing with densely or vascular-rich adhesions, particularly those around the hepatic hilum or major [16][17][18]. In our study, similar results were obtained in laparoscopic when compared with open liver re-resection.…”
Section: Discussionsupporting
confidence: 93%
“…Dealing with densely or vascular-rich adhesions, particularly those around the hepatic hilum or major [16][17][18]. In our study, similar results were obtained in laparoscopic when compared with open liver re-resection.…”
Section: Discussionsupporting
confidence: 93%
“…However, JM Wu et al, concluded that previous abdominal surgery, whether upper or lower abdominal, has no significant impact on laparoscopic appendectomy for acute appendicitis. 9 Raised total leucocyte count or raised neutrophil level does not affect the difficulty in performing laparoscopic appendectomy. Similarly raised LFT like serum bilirubin, AST, ALT also has no significant role in predicting the difficulty of laparoscopic cholecystectomy.…”
Section: Discussionmentioning
confidence: 97%
“…[25] Although a history of abdominal surgery had been considered a contraindication for laparoscopic surgery in the early days of the procedure, improvements in technique and instrumentation have more recently permitted many laparoscopic procedures to be safely applied to such patients. [24,[26][27][28][29] However, LLR remains a technically demanding procedure and the indications for and efficacy of repeat LLRs are still under discussion. Successful liver resection requires adequate adhesiolysis and mobilization of the involved liver area.…”
Section: Discussionmentioning
confidence: 99%